A new strategy: fermi level control to realize 3D pyramidal NiCo-LDH/ReS2/n-PSi as a high-performance photoanode for the oxygen evolution reaction. Issue 10 (16th February 2022) - Zhao, Yingzhi; Song, Weiming; Li, Zhiyong; Zhang, Zhang; Zhou, Guofu
Abstract : ReS2 nanosheets have been grown on n-type Si substrate as photoanode for OER. By introducing pyramid Si and NiCo-LDH co-catalyst, the photocurrent of NiCo-LDH/ReS2 /n-PSi was boosted from 0, 31 mA cm −2 of ReS2 /n-Si to 1.74 mA cm −2 . Abstract : Loading ReS2 nanosheets (NSs) on a planar p-type doping Si substrate has been proved to work well in photoelectrochemical (PEC) water splitting for the hydrogen evolution reaction (HER). The high PEC performance is attributed to the p–p junction for accelerating charge separation and the two dimensional (2D) light trapping effect for enhanced light absorption. Herein, we report a novel photoanode for the oxygen evolution reaction (OER) which is composed of an n-type pyramid-pattern Si substrate and p-ReS2 NSs. Compared to planar ReS2 /p-Si, the p–n junction of ReS2 /n-PSi can achieve a much higher photocurrent due to more upward band bending, while more light absorption comes from the 3D anti-reflection structure. By avoiding near-surface downward band bending and enhancing charge transportation, the earth-abundant co-catalyst, NiCo-layered double hydroxides (NiCo-LDH), was finally deposited to boost the photocurrent of the NiCo-LDH/ReS2 /n-PSi photoanode into the competitive mA cm −2 range (1.74 mA cm −2 ). The NiCo-LDH cover layer can also improve the stability of the photoanode by acting as a protective layer. Thus, it is a new concept for ReS2 /Si to work as a high-performance photoanode for the OER through Fermi level control and a split-new solution to deal with the energy barrier caused by the work function of different surface materials in a dual photoelectrode system.